Scientific and Methodological Aspectsof Risk Accounting in an Organization - Tat’yana Yur’evna Serebryakova (Учёт. Анализ. Аудит)
Subject. The article deals with the current trend towards applying the risk-based approach to all managerial and control processes. It systemizes the basic models of risk management and their elements, analyzes the rules of risk accounting applied in tax and financial accounting and eventually concludes that existing standards of risk management do not contain requirements to risk accounting and that risk accounting for financial and tax accounting purposes does not take into consideration the tasks of risk management. Purpose. The objective of the research is to study the category of accounting as a tool of risk management in order to understand the importance and necessity of risk accounting in a special accounting system and to determine the main principles for such accounting. Methodology. The author uses general scientific methods of cognition: a systematic approach, logic synthesis, legal analysis, linguistic analysis, hypothesis. Results. To manage risk means to control it and take prompt actions. Control is not possible without taking into account the object of control and its special features. To account for risks it is necessary to build a system in which the object of accounting would be risks. Strictly speaking, risk by itself is not a financial indicator. In the system of financial accounting of risks the accounting object should be the anticipated consequences of risks, expressed in monetary terms. All accounting systems are based on the goals, events and indicators that are subject to monitoring. The same principles can be used as a foundation for a system of risk accounting in monetary terms, where the accounting unit would be positive and negative consequences of events that carry risk. Conclusions. It is necessary to create a special system of risk accounting based on the principles of modeling, balance generalization, evaluation and double entry. On the basis of risk management understanding and the author’s classification of the events involving risks the article makes proposals about the organization of risk accounting for risk management purposes.